Fractured porous media - Adler, Pierre M.; Thovert, Jean-Francois.; Mourzenko, Valeri V. (Oxford : Oxford University Press, 2013)
This book provides a systematic treatment of the geometrical and transport properties of fractures, fracture networks, and fractured porous media. It is divided into two major parts. The first part deals with geometry of individual fractures and of fracture networks. The use of the dimensionless density rationalizes the results for the percolation threshold of the networks. It presents the crucial advantage of grouping the numerical data for various fracture shapes. The second part deals mainly with permeability under steady conditions of fractures, fracture networks, and fractured porous media. Again the results for various types of networks can be rationalized by means of the dimensionless density. A chapter is dedicated to two phase flow in fractured porous media--
Includes bibliographical references (p. [167]-172) and index.
Keywords: Percolation; Fracture mechanics; Porous materials